The Influence of Organizational Culture, Work Environment, and Leadership Style on Employee Performance - Asrianto; Mattalatta; Sandra, Kurniawaty; Ansar; Bata Ilyas, Gunawan (Cendekiawan Indonesia Timur, 2025)
Employee performance is a crucial factor in ensuring the sustainability and competitiveness of organizations. This study aims to analyze the impact of organizational culture, work environment, and leadership style on employee performance, with innovation as a mediating variable at PT. Telkomsel Branch Makassar. The research is based on organizational sociology and human resource management theories, which emphasize the importance of internal corporate factors in enhancing productivity and achieving business objectives. The study explores how these factors interact to influence employees' ability to contribute effectively to organizational goals. A quantitative research approach was employed, utilizing a survey method conducted among employees of PT. Telkomsel Branch Makassar. Data were collected through structured questionnaires and analyzed using inferential statistical methods to examine the relationships among the research variables. The results indicate that organizational culture, work environment, and leadership style positively affect employee performance. Furthermore, innovation plays a significant mediating role, strengthening the relationship between these factors and employee performance. The findings suggest that organizations should foster a culture that supports innovation, provide a conducive work environment, and implement leadership styles that encourage creativity and active employee participation. By enhancing these aspects, companies can improve employee performance and overall corporate success. This study contributes to the growing body of research on employee performance management, particularly within the telecommunications industry. The practical implications emphasize the need for companies to continuously adapt their organizational strategies to remain competitive in an evolving business landscape.